Rosenberg (white blazer, dark trousers) shakes hands with the collaborators of the "Reichskommissariat Ukraine" and the "Einsatzstab Reichsleiter Rosenberg"
Rosenberg (white blazer, dark trousers) shakes hands with the collaborators of the "Reichskommissariat Ukraine" and the "Einsatzstab Reichsleiter Rosenberg".